2019
DOI: 10.3389/fncel.2018.00505
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus Type 1 Enhances Expression of the Synaptic Protein Arc for Its Own Benefit

Abstract: Herpes simplex virus type 1 (HSV-1) is a neurotropic virus able to reach the central nervous system (CNS) after primary infection in oronasal mucosa. HSV-1 establishes latency inside neurons due the repression of its gene expression process, which is related to periodic reactivations in response to cellular stress conditions, constituting a risk factor for neurodegenerative diseases such as Alzheimer’s disease (AD). The immediate-early gene Arc plays an essential role in neuronal morphology, synaptic plasticit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 56 publications
(81 reference statements)
1
12
0
Order By: Relevance
“…In a recent report we demonstrated induction and altered distribution of Arc protein during HSV-1 infection in several neuronal cell lines; HT22: mouse hippocampal neurons, SH-SY5Y human neuroblastoma and H4: human neuroglioma. Our findings strongly suggest that pathogenicity of HSV-1 neuronal reactivations in humans could be mediated in part by Arc upregulation [18].…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In a recent report we demonstrated induction and altered distribution of Arc protein during HSV-1 infection in several neuronal cell lines; HT22: mouse hippocampal neurons, SH-SY5Y human neuroblastoma and H4: human neuroglioma. Our findings strongly suggest that pathogenicity of HSV-1 neuronal reactivations in humans could be mediated in part by Arc upregulation [18].…”
Section: Discussionmentioning
confidence: 51%
“…Thus, Arc protein interacts with distinct protein partners to participate in the regulation of multiple forms of synaptic plasticity [17]. Interestingly, we previously demonstrated that HSV-1 acute infection increases Arc mRNA and protein expression in different neuronal cell lines, and the up-regulation is dependent of an active viral replicative cycle [18]. Nevertheless, the impact of HSV-1 infection on dendritic spines, dendritic arborization and Arc signalling, are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Immunosenescence affects this response, making the brain vulnerable to infectious agents [ 14 - 15 ]. HSV1 has been proposed as a potential risk factor in the development of AD [ 1 - 4 , 8 , 11 , 13 - 14 , 17 - 19 , 21 , 24 - 25 , 29 , 31 , 33 - 39 ]. A meta-analysis by Steel et al concluded that there is an increased risk for AD when HSV1 is present in the brain compared to controls (OR 1.38; 95% CI 1.14-1.66) [ 35 ].…”
Section: Reviewmentioning
confidence: 99%
“…Herpes simplex virus type-1 (HSV1) is a highly neurotropic, double-stranded deoxyribonucleic acid (DNA) virus [2][3][4]7,11,[14][15][16][17]19,21,25,[29][30][31]. It is a ubiquitous pathogen that affects 80%-90% of the US population by the sixth decade, with persisting serum antibodies [2][3]7,11,14,17,24].…”
Section: Introductionmentioning
confidence: 99%
“…Cognition-related neuronal gene Arc was demonstrated to migrate from neuron to neuron in a retroviral fashion, possibly linking antiretroviral drugs to cognition (Ashley et al, 2018; Pastuzyn et al, 2018). Interestingly, HSV1 was associated with altered transcription of Arc, linking this virus once again to neuronal senescence and memory loss (Penner et al, 2010; Bi et al, 2018; Acuña-Hinrichsen et al, 2019; Man et al, 2019). This finding is in line with novel epidemiological studies that have connected HSV1 to cellular senescence and AD (Dowd et al, 2017).…”
Section: Beta Amyloid: Friend or Foe?mentioning
confidence: 99%